Some Considerations About Kesh, The Political and Cultural Center of Sugd in the Early Middle Ages (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the position of the city of Kesh as the political and cultural center of Sugd in the early Middle Ages, the historical geographical classification of the state and region of Kesh in Chinese historical sources, the fact that the territories from the Chu River to Shakhrisabz were called the Land of the Sulik, the fact that the city of Kesh was one of the political, cultural and economic centers of Sugd in antiquity and the early Middle Ages, and the fact that the city of Kesh was one of the developed centers of Sugd in cultural and international relations based on historical sources, including Chinese sources.